RETRACTED: Mast Cells in Skin Scarring: A Review of Animal and Human Research - Ud-Din, Sara; Wilgus, Traci A.; Bayat, Ardeshir (Frontiers in Immunology, 2020)
Mast cells (MCs) are an important immune cell type in the skin and play an active role during wound healing. MCs produce mediators that can enhance acute inflammation, stimulate re-epithelialisation as well as angiogenesis, and promote skin scarring. There is also a link between MCs and abnormal pathological cutaneous scarring, with increased numbers of MCs found in hypertrophic scars and keloid disease. However, there has been conflicting data regarding the specific role of MCs in scar formation in both animal and human studies. Whilst animal studies have proved to be valuable in studying the MC phenomenon in wound healing, the appropriate translation of these findings to cutaneous wound healing and scar formation in human subjects remains crucial to elucidate the role of these cells and target treatment effectively. Therefore, this perspective paper will focus on evaluation of the current evidence for the role of MCs in skin scarring in both animals and humans in order to identify common themes and future areas for translational research.